Cross-border mergers and national champions in an integrating economy - Jens Suedekum (Institute for the Study of Labor (IZA), 2006)
We introduce a simple oligopolistic trade model with international transportation costs, and analyze the profitability and the social desirability of national vs. international mergers in relation to three different issues, (i) the level of trade freeness, (ii) the possibility of rent appropriation on world markets, and (iii) direct synergy effects of mergers. Cross-border M&A is privately and socially more attractive than domestic mergers. National competition policy may be too permissive towards M&A, because it does not take into account the negative impact of decreasing competition on world consumer surplus. We also discuss the normative implications of national champions. The promotion of national mergers can be in the interest of individual countries if rent extraction possibilities are strong enough, but global welfare is adversely affected.
Keywords: F12; F23; L13; L52; 330; mergers; national champions; international trade; economic integration